Effects of post-processing on the microstructural evolution and mechanical behaviour of an additively manufactured AlSi10Mg alloy - R. Ramesh; Saurabh Gairola; R. Jayaganthan; M. Kamaraj (Journal of Materials Research and Technology)
AlSi10Mg alloy finds critical applications in the automotive sector, such as in cylinder heads, engine blocks, and wheels. Such applications often require intricate parts that can be fabricated only through additive manufacturing. In this context, the fatigue life of the additively manufactured components is crucial to prevent sudden failure during real-life application. The post-processing techniques such as heat treatment (HT) and shot blasting (SB) have the potential to enhance the fatigue performance of AlSi10Mg. However, their effectiveness in improving fatigue properties has not been explored so far. Hence, this study examines the effect of the combination of HT and SB on the fatigue life of AlSi10Mg alloy. The fatigue strength of the Laser Powder Bed Fusion (LPBF) increases from 43 MPa in the as-built (AB) condition to 44.5 MPa in the HT + SB condition. The strengthening mechanisms contributing to the high tensile and fatigue strength in different conditions were explored using various microscopy techniques such as Scanning Electron Microscope (SEM) and Electron Back-Scattered Diffraction (EBSD). Silicon precipitates, in the form of cellular structures and spherical forms, were found to significantly contribute to the strength of an alloy, accounting for 63%, 52%, and 50.7% of the total strength in AB, HT and HT + SB conditions, respectively.